2015
DOI: 10.5603/cj.a2015.0045
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS complexes are associated with left ventricular systolic and diastolic dysfunctions in patients with metabolic syndrome

Abstract: 041). MetS was associated with subclinical LV systolic and LV diastolic dysfunctions. In subgroup analyses of MetS patients, the presence of fQRS on ECG had a higher E/E' ratio and lower E' velocity, indicating pronounced diastolic dysfunction, as well as lower isovolumic acceleration (IVA), indicating profound subclinical LV systolic dysfunction. E/E' ratio and IVA were independent predictors of fQRS presence in patients with MetS. Conclusions: Fragmented QRS is more common among MetS patients compared to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
(39 reference statements)
1
15
2
Order By: Relevance
“…3 In healthy smokers, coronary flow reserves are affected and the outcome of the variation in coronary circulation not meeting myocardial oxygen requirements causes diastolic function disorder. [16][17][18][19] In our study, this rate was 18.4%, which is higher than non-smokers healthy individuals. To identify myocardial fibrosis, histopathological evaluation, cardiac magnetic resonance imaging, and scintigraphy may be used; however, these methods are expensive and may be difficult to access.…”
Section: Discussioncontrasting
confidence: 49%
“…3 In healthy smokers, coronary flow reserves are affected and the outcome of the variation in coronary circulation not meeting myocardial oxygen requirements causes diastolic function disorder. [16][17][18][19] In our study, this rate was 18.4%, which is higher than non-smokers healthy individuals. To identify myocardial fibrosis, histopathological evaluation, cardiac magnetic resonance imaging, and scintigraphy may be used; however, these methods are expensive and may be difficult to access.…”
Section: Discussioncontrasting
confidence: 49%
“…The fQRS has also been found to be associated with subtle myocardial dysfunction in several reports. Oner et al evaluated patients with metabolic syndrome and compared them with matched control individuals without metabolic syndrome. They observed that fQRS was more common among patients with metabolic syndrome compared to those without it (26.1% vs 14.6%, P = .041).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a population‐based study in Finland, the rate of healthy individuals with fQRS was 18.3% (1518 of 8277 individuals without known cardiac diseases), and it has been found to be 14.6% among a healthy population in a case‐control study . In contrast, the prevalence of fQRS in other population is significantly greater than healthy population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that EAT was independently associated with presence of fQRS. fQRS on ECG has been regarded as a marker of myocardial fibrosis or scarring in different diseases and independent predictor of cardiac events in patients with coronary artery disease (9)(10)(11) .…”
Section: Discussionmentioning
confidence: 99%